Utility of trans-vaginal ultrasound in diagnosis and follow-up of non-pregnant sexually active females with lower ureteric calculi - Siddharth Pandey; Tanica Pandey; Apul Goel; Ajay Aggarwal; Deepanshu Sharma; Tushar Pandey; Satya sankhwar; Gaurav Garg (Asian Journal of Urology)
Objective: To assess the utility of trans-vaginal ultrasonography in evaluation of non-pregnant sexually active female patients with lower ureteric calculi. Methods: A prospective study was done from January 2015 to December 2017 including non-pregnant sexually active females with suspected ureteric calculus. Trans-abdominal ultrasound was initially done in all patients. In those patients in whom trans-abdominal ultrasound was inconclusive or there was indirect evidence of lower ureteric calculus in form of ureteral dilation but no calculus was evident, trans-vaginal ultrasound was done. The patients with ureteric calculi detected on trans-vaginal ultrasound and kept on conservative management were also followed up with trans-vaginal ultrasound. Non-contrast computed tomography was done in patients with inconclusive trans-vaginal ultrasound. Results: As per the study protocol, 156 out of the total 468 patients evaluated by trans-abdominal ultrasound were eligible for trans-vaginal ultrasound. Trans-vaginal ultrasound was done in 149 patients, as seven patients did not give consent. Seventy-nine patients were detected with a lower ureteric calculus on trans-vaginal ultrasound and 27 patients had gynecologic or other cause for their symptoms. Forty-three patients had an inconclusive trans-vaginal ultrasound of which 36 underwent non-contrast computed tomography, among them only one patient had a lower ureteric calculus. Stone free status could be easily demonstrated on follow-up trans-vaginal ultrasound. Conclusion: Trans-vaginal ultrasound in addition to trans-abdominal ultrasound is a very useful tool in evaluation of sexually active females with suspected lower ureteric calculus. Keywords: Trans-abdominal ultrasound, Trans-vaginal ultrasound, Lower ureteric calculus, Ureteric colic, Ureter